FIGURATIVE LANGUAGE IN SOLEDAD SONG BY WESTLIFE - Hasby, M. Asrul; Muhlisin, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2018)
This thesis is aimed to know the figurative language in soledad song.The method of the research was descriptive qualitative, where in this research, the researcher as object of the study the key instrument the data gathering used four steps such as: Documentation technique, identifying, coding and listening. The data analysis used data reduction,data display, and drawing conclusion or verification data. From the discussion it can be concluded that the lyric of Westlife’s song use six figurative language: (1) hyperbole (2) personification (3) metahor (4) paradox (5) symbol(6) paralellism. The researcher found fourteen expression from that and the most frequently appear is hyperbole and paradox. Therefore the conclusion of the research was six kinds of figurative language that appear in Soledad Song by westlife